2y-3=1y-8

Simple and best practice solution for 2y-3=1y-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2y-3=1y-8 equation:


Simplifying
2y + -3 = 1y + -8

Reorder the terms:
-3 + 2y = 1y + -8

Reorder the terms:
-3 + 2y = -8 + 1y

Solving
-3 + 2y = -8 + 1y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-1y' to each side of the equation.
-3 + 2y + -1y = -8 + 1y + -1y

Combine like terms: 2y + -1y = 1y
-3 + 1y = -8 + 1y + -1y

Combine like terms: 1y + -1y = 0
-3 + 1y = -8 + 0
-3 + 1y = -8

Add '3' to each side of the equation.
-3 + 3 + 1y = -8 + 3

Combine like terms: -3 + 3 = 0
0 + 1y = -8 + 3
1y = -8 + 3

Combine like terms: -8 + 3 = -5
1y = -5

Divide each side by '1'.
y = -5

Simplifying
y = -5

See similar equations:

| y=3/2(-6)-6 | | 19x-5=14x-10 | | 1/6m=3/20 | | x^2+3x-5/2x-1 | | 8x+14=5x+5 | | 6m+7.25=58.25 | | 1/4x-1/6x=4 | | 8x-3=2x+5 | | 3x^2-10y+3=0 | | n-14=4 | | 6y-4=5y+2 | | x+9=3x-3 | | 3r^2+8r+5=0 | | 2n-10=10 | | 8x-5+6=4x+1 | | m*6=70 | | 4(3x+7)=-33+49 | | z+3/6+1=2z+7/4 | | 15b+3=11b-4 | | -0.8x+0.3x-6=-7 | | -8.9+5x-6.3+3x-2.5=5.6+9x+1.2 | | (x+6)/4-(x)/2=-x | | 3x-52=26 | | 4[2x+5]-8=36 | | 2n-15=19 | | 7w/4+3=9w/10+6 | | -x+3=16 | | 3a+2=5a-3 | | 10n-5=65 | | -5/7*7/5=-1 | | 5k^4/36k^4 | | 5x=6x+2 |

Equations solver categories